Examining the Role of a Private-Order Institution in Global Trade: The Liverpool Cotton Brokers' Association and the Crowning of King Cotton, 1811–1900. Issue 4 (2021) - Aldous, Michael; Coyle, Christopher
Abstract : In the nineteenth century, the Liverpool Cotton Brokers' Association (CBA) coordinated the dramatic growth of Liverpool's raw cotton market. This article shows how the CBA achieved this through the development of a private-order institutional framework that improved information flows, introduced standardization and contracting regimes, and regulated market exchange platforms. These developments corresponded with significantly improved market coordination, which facilitated the growth of the largest raw cotton market in the world. The article's findings demonstrate and quantify the importance of nonstate actors in creating institutions of global exchange central to the first wave of globalization.